PENGUJIAN ANTI AGING SEDIAAN KRIM CANGKANG BEKICOT (ACHATINA FUNICA) PADA KELINCI (ORYCTOLAGUS CUNICULUS) YANG DIPAPAR SINAR UV - Muhammad Asri; Nielma Auliah (Politeknik Kesehatan Makassar, 2019)
Snail shells is one of the mollusk phyla that contains protein and chitin function as protector from wind. The protector of wind is a process to prevent premature of the skin. This research aimed to find the formulation and efficacy test of snail shel cream (Achatina fulica) on rabbits (Oryctolagus cuniculus) as protector from the wind .The type of this research used experimental method with UV exposure method using Philips light intensity 10 Mw/cm2 where the back skin of animals try to be wrinkled. The samples of snail shells (Achatina fulica) used the powdered shell is then used as the active compound in the cream dosage formulation. Cracked cream shell powder formulas are formulated in four formulas with concentration 0% (without cracked cream shell powder) 5%, 10%, 15%, and testing the skin of the rabbit’s back (Oryctolagus cuniculus). Treatment is divided into 5 treatments namely treatment 1 as positive control used cream without active compound, treatment 2 concentration cream 5%, treatment 3 concentration cream 10%, treatment 4 concentration cream 15%, and treatment 5 as negative control used cream patent as the protector of x wind. The result of this research showed the effectivitas of concentration cream 5% which had 16,4 mm, and the positive control had 5,7 mm. It can conclude that with concentration 5% had the most powerful effectiveness than variation in the concentration of other creamsKeywords : Snail shells (Achatina fulica), Formulation, The protector of wind